Reproducción de la sardina, Sardinella aurita (Cupleiformes: Clupeidae) del sureste de la Isla de Margarita, Venezuela - Gassman, Juan; Eslava, Nora; González, Leo W. (Revista de Biología Tropical, 2008)
Sex ratio, sexual maturity, fecundity and time of spawning of the Spanish sardine (Sardinella aurita) from the south-eastern area of Margarita Island were determined through monthly samplings of commer-cial fisheries, from January 2004 to April 2005. A total of 3 736 individuals were examined. Sex ratio was 55.47% females and 44.53% males, with a 1:1.25 sexual proportion (χ2 = 44.454, p< 0.05). Length at first sexual maturity (L50) was 20 cm. Spawning of the species was confirmed to be partial and continuous throughout the year, with two peaks of intensity during the first and last quarters. Absolute fecundity ranged from 10 530 to 83 779 oocytes and it was proportional to body length (F = - 100 900 + 6 696.2 * L) and to body weight (F = 13 327 + 5 666.3 * P). Relative fecundity ranged from 149 to 1 020 oocytes/g and also was proportional to body length and weight. We concluded that the Spanish sardine exhibits two peaks of spawning activity per year with a very fluctuating partial fecundity which could possibly be explained by environmental variability.